Pengaruh Islamic Social Reporting dan Islamic Corporate Governance Terhadap Return On Asset Dengan Intellectual Capital Sebagai Variabel Moderasi (Studi Pada Bank Umum Syariah Yang Terdaftar di OJK Tahun 2018-2022) - Reski; Saiful Muchlis; Namla Elfa Syariati (Indonesian Journal of Taxation and Accounting, 2024)
This study aims to determine the influence of Islamic social reporting and Islamic corporate governance on return on assets with intellectual capital as a moderation variable in Sharia Commercial Banks registered with the OJK in 2018-2022. This research is a type of quantitative research with a comparative causal approach. The data used is in the form of secondary data in the form of annual reports and good corporate governance for the 2018-2022 period which is accessed through the official website of each bank. In this study, 40 samples were used with a side purposive method. This study uses analysis techniques in the form of multiple linear regression analysis and moderation regression analysis with the help of the SPSS 29 program. Based on the results of this study, it shows that the results of Islamic social reporting and Islamic corporate governance have a positive effect on return on assets, then the intellectual capital variable is not able to moderate the influence of Islamic social reporting, Islamic corporate governance on return on assets. The implication of this study is that it can be a reference in decision-making to improve financial performance which is proxied by return on assets in Sharia Commercial Banks.